Capital Structure Determinants: The Role of Non-Debt Tax Shield, Cash Holding, and Growth Opportunity - Rizkyana, Rizkyana; Ning Tandayu, Woro; Sri Lastanti, Hexana (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2025)
Backgrounds: The basic and chemical industrial sector was selected for its significance in supplying everyday products and its capacity to aid businesses in optimizing financial strategies and attracting investors. Objectives: This study will examine the influence of Non-Debt Tax Shield, Cash Holdings, and Growth Opportunities on Capital Structure in basic and chemical manufacturing companies listed on the Indonesia Stock Exchange. Methods: This study employs a census sampling method, resulting in 12 pharmaceutical companies listed on the IDX throughout a seven-year duration, culminating in a total sample size (n) of 84. The research employs a causal associative methodology and utilizes multiple linear regression analysis to ascertain the relationship between the independent and dependent variables. Results: The results indicate that at a 5% significance level, all three variables exerted a significant impact on the dependent variable. The ANOVA test findings indicate that the regression model employed in this analysis is significant, as evidenced by an F-statistic exceeding the crucial value and a significance level below 0.05.